Nanosecond Imaging of Shock- and Jet-Like Features - Tubman, E; Crowston, R; Alraddadi, R; Doyle, H; Meinecke, J; Cross, J; Bolis, R; Lamb, D; Tzeferacos, P; Doria, D; Reville, B; Ahmed, H; et al. (Institute of Electrical and Electronics Engineers Inc., 2014)
The production of shock-and collimated jet-like features is recorded from the self-emission of a plasma using a 16-frame camera, which can show the progression of the interaction over short (100s ns) durations. A cluster of laser beams, with intensity 1015 W/cm2 , was focused onto a planar aluminum foil to produce a plasma that expanded into 0.7 mbar of argon gas. The acquisition of 16 ultrafast images on a single shot allows prompt spatial and temporal characterization of the plasma and enables the velocity of the jet-and shock-like features to be calculated.